THE SOVIET ELECTIONS IN TRANSCARPATHIA ACCORDING TO PRESS MATERIALS: PUBLIC MOOD AND THE POSITION OF THE UKRAINIAN INSURGENTS - Sakal, Myroslav (Young Scholars Grinchenko – Seton International Journal, 2026)
This paper explores the conduct of Soviet election campaigns in the Transcarpathian region of the Ukrainian SSR during 1946 – 1947. The study focuses on the region’s mountainous settlements, using the Svaliava district as a representative administrative-territorial unit of that period. The main feature of this research is the selection of local periodicals as the primary source, which allows for a more detailed micro-historical investigation. Through careful analysis of contemporary periodicals and archival materials, it is possible to uncover events that were highlighted not only through an ideological lens but also through local social conflicts, administrative decisions, and public reactions. Furthermore, this study allows us to trace whether the level of censorship in the local press was truly as extensive as often assumed. Even within Soviet publishing houses, there were editors and authors who could criticize local officials. However, this dynamic could work both ways. On the one hand, some editors and authors condemned specific officials for their actions; on the other hand, there were those who condemned the residents of individual settlements for failing to meet assigned targets set for ideological and propaganda purposes. The paper analyzes the methods of Soviet political integration alongside public reaction and the resistance efforts of the Ukrainian underground.